2022
DOI: 10.1108/mrr-08-2021-0595
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunications service quality, customer satisfaction and customer loyalty in pandemic times

Abstract: Purpose This study aims to empirically explore telecommunications service quality (SQ) and its impact on the customer loyalty (CL) through a mediating impact of customer satisfaction (CS) during the COVID-19 pandemic crisis. Design/methodology/approach A survey was conducted involving 384 customers of telecommunications service providers in Egypt. The hypothesized direct relationships were tested through regression analysis, and the mediating effect was tested using structural equation modeling technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(101 reference statements)
0
0
0
Order By: Relevance
“…The empirical results indicated a positive and significant correlation of all five service quality dimensions with customer satisfaction in the context of Nepalese cell phone service providers, which is consistent with the findings of many previous studies (Abd-Elrahman, 2023;Bhagat, 2014;Fen & Lian, 2005;Ojo, 2010;Safi & Alagha, 2020;Shava, 2021;Shrestha & Ale, 2019). The findings indicated that the companies still need to improve their service quality.…”
Section: Note N = 336supporting
confidence: 88%
“…The empirical results indicated a positive and significant correlation of all five service quality dimensions with customer satisfaction in the context of Nepalese cell phone service providers, which is consistent with the findings of many previous studies (Abd-Elrahman, 2023;Bhagat, 2014;Fen & Lian, 2005;Ojo, 2010;Safi & Alagha, 2020;Shava, 2021;Shrestha & Ale, 2019). The findings indicated that the companies still need to improve their service quality.…”
Section: Note N = 336supporting
confidence: 88%
“…It is influenced by customer expectations and perceptions, and can be measured through models like SERVQUAL and IPA (Kitchroen, 2004). The dimensions of service quality include tangible, reliability, responsiveness, assurance, and empathy (Verma, 2020). It is a key focus for service academics, requiring a framework for planning, design, and implementation (Prakash & Mohanty, 2013).…”
Section: Service Qualitymentioning
confidence: 99%
“…The surge in demand for pharmaceutical products and healthcare services during the pandemic has led to a notable shift in customer behavior compared to pre-pandemic times [13]. It is imperative to comprehend the sentiments, behaviors, and thoughts of customers regarding the use of pharmaceutical products and the acquisition of services from clinics and pharmacies in this altered landscape.…”
Section: ) Strains In Hospitals Due To Lack Of Community Pharmaciesmentioning
confidence: 99%